Personal Growth and Well-Being in the Time of COVID: An Exploratory Mixed-Methods Analysis - Kim, Juensung J.; Munroe, Melanie; Feng, Zhe; Morris, Stephanie; Al-Refae, Mohamed; Antonacci, Rebecca; Ferrari, Michel (Frontiers in Psychology, 2021)
The physical distancing measures forced by COVID-19 have resulted in a mass withdrawal from the patterns of daily life, necessitating significantly reduced contact with other people. To many, such withdrawal from the world can be a major cause of distress. But to some, this sort of retreat is a necessary part of growth, a pathway to a more enriching life. The present study uses a sequential explanatory QUAN-qual design to investigate whether there were people to be found who felt that their lives had actually changed for the better after being forced into physical distancing conditions, what factors predicted such well-being, and how they spent their time such that this sense of well-being might be possible. 614 participants who reported closely following physical distancing recommendations were invited to complete the survey. Our analyses found that while religiosity, current health, personal wisdom, social support, and presence of meaning in life were positive predictors of participants’ current well-being, presence of meaning in life, coping style, and self-transcendent wisdom were the sole predictors of increased well-being from before the beginning of physical distancing measures. Correspondingly, an extreme case content analysis of participants’ personal projects found that participants reporting low self-transcendent wisdom tended to report more survival-oriented projects, such as acquiring groceries or engaging in distracting entertainments, while participants reporting high self-transcendent wisdom reported more projects involving deepening interactions with other people, especially family. Our findings add new nuance to the pathway from adversity to a deeper sense of well-being, by demonstrating the importance of not merely coping with or reacting to adversity, but truly transcending it.